2019
DOI: 10.1111/1348-0421.12718
|View full text |Cite
|
Sign up to set email alerts
|

Essential domains of phosphatidylinositol‐4 kinase III β required for enterovirus replication

Abstract: Phosphatidylinositol‐4 kinase III β (PI4KB) is a host factor that is required for enterovirus (EV) replication. In this study, the importance of host proteins that interact with PI4KB in EV replication was analyzed by trans complementation with PI4KB mutants in a PI4KB‐knockout cell line. Ectopically expressed PI4KB mutants, which lack binding regions for ACBD3, RAB11, and 14‐3‐3 proteins, rescued replication of poliovirus and enterovirus 71. These findings suggest that interaction of PI4KB with these host pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Moreover, I44 and H54 are important for stabilizing the ACBD3-PI4KB complex and are critical for EV-A71 replication (Xiao et al, 2017). Surprisingly, a recent study on trans-rescue of EV-A71 pseudovirus replication with PI4KB deletion mutants suggested that ACBD3-binding site of PI4KB is not essential for EV-A71 replication (Arita, 2019). The role of ACBD3-PI4KB interaction involved in EV-A71 infection need to be further investigated.…”
Section: Acbd3 In Enterovirus Infection Enterovirus A71 (Ev-a71)mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, I44 and H54 are important for stabilizing the ACBD3-PI4KB complex and are critical for EV-A71 replication (Xiao et al, 2017). Surprisingly, a recent study on trans-rescue of EV-A71 pseudovirus replication with PI4KB deletion mutants suggested that ACBD3-binding site of PI4KB is not essential for EV-A71 replication (Arita, 2019). The role of ACBD3-PI4KB interaction involved in EV-A71 infection need to be further investigated.…”
Section: Acbd3 In Enterovirus Infection Enterovirus A71 (Ev-a71)mentioning
confidence: 99%
“…They demonstrated that ACBD3 promoted PV replication by more than 10-fold (Lyoo et al, 2019). A recent study on trans-rescue of PV1 pseudovirus replication with PI4KB deletion mutants showed that ACBD3-binding site of PI4KB is not essential for PV1 pseudovirus replication (Arita, 2019). Whether the interaction of ACBD3-PI4KB is involved in bona fide PV1 infection need more studies to clarify.…”
Section: Poliovirus (Pv)mentioning
confidence: 99%
“…While PHB and APOLs seem to be part of an autophagy system linked to infection, PI4KB is likely to be associated with this system given involvement of this enzyme in both autophagy and viral replication [56,118–131]. Accordingly, PI4KB was found to be involved in autophagy linked to infection by group A Streptococcus [144].…”
Section: Apols and Viral Infectionmentioning
confidence: 99%
“…3). PI4KB is also crucially involved in the PI (4)P-dependent remodelling of cellular membranes induced by different viruses in order to build membranous structures such as replication organelles or inclusion bodies, where new virions are assembled [118][119][120][121][122][123][124][125][126][127][128][129][130] (review in Ref. [131]).…”
Section: Apols and Viral Infectionmentioning
confidence: 99%
“…However, PI4KB and ACBD3 recruitment by CVB3 and HRV 3A likely independent of GBF1/Arf1 and ACBD3 (Dorobantu et al, 2014(Dorobantu et al, , 2015. And recent research about PI4KB using trans complementation with PI4KB mutants in a PI4KB-knockout cell line shows that interaction of PI4KB with host proteins (ACBD3, RAB11A, and 14-3-3) is not essential for EV replication once PI4KB has been expressed and that PI4KB is functionally independent from host proteins regarding EV replication (Arita, 2019). They are different from the above results, which may be due to the use of siRNA to knock down endogenous GBF1 and ACBD3 levels but not cause a complete knock out.…”
Section: Pimentioning
confidence: 99%